Diagnosis of Community-acquired Pneumonia in Hospitalized Children: A Multicenter Experience in Bolivia. Issue 1 (January 2021) - Gareca Perales, José; Soleto Ortiz, Lorena; Loayza Mafayle, Roxana; Machuca Soto, Blanca; Hidalgo Flores, Lucia; López Montaño, Javier; Zuna Calle, Neida; Jarovsky, Daniel; Naaman Berezin, Eitan
Abstract : Background: Community-acquired pneumonia (CAP) represents a major cause of hospitalization, especially among young children. In the third world countries, information about CAP etiology is scarce. Therefore, rapid and highly sensitive diagnostic methods are crucial to determine etiologic agents. Methods: Between March 2016 and March 2017, we have prospectively studied the clinical, radiologic, laboratory, and molecular aspects of patients with CAP at 2 tertiary-level hospitals in Santa Cruz de la Sierra, using a multiplex real-time polymerase chain reaction (RT-PCR). Results: A total of 274 children were evaluated, with a median age of 13 months. An etiologic agent was identified in 187 patients (68.2%): 54% (n = 148) were viruses and 14.2% (n = 39) were bacteria. CAP prevalence was highest among children under 2 years (71%; 195/274); respiratory syncytial virus (RSV) was the most frequent cause in 22% (60/274), especially among infants, followed by influenza (14.5%; 40/274). Streptococcus pneumoniae accounted for 7% of the total (19/274), followed by Staphylococcus aureus (3%;8/274) and Haemophilus influenzae (1.4%;4/274). Together, these cases accounted for 79.5% (31/39) of all bacterial CAP. Pleural effusion (PE) complicated CAP in 13.8% (38/274), of which 29 were of bacterial etiology. RT-PCR increased the detection rate of pneumococcus by 47%. Coinfection occurred in 28 patients (10%); 26 (9.5%) required intensive care and 9 patients (3%) died. Conclusions: RT-PCR provided additional diagnostic value to conventional, clinical, and laboratory methods. The higher prevalence of RSV, influenza, and Streptococcus pneumoniae reveals the need for preventive measures with better vaccine uptake and future research for RSV vaccines. Abstract : Supplemental Digital Content is available in the text.